Basal Forebrain Atrophy Contributes to Allocentric Navigation Impairment in Alzheimer’s Disease Patients - Kerbler, Georg M.; Nedelska, Zuzana; Fripp, Jurgen; Laczó, Jan; Vyhnalek, Martin; Lisý, Jiří; Hamlin, Adam S.; Rose, Stephen; Hort, Jakub; Coulson, Elizabeth J. (Frontiers in Aging Neuroscience, 2015)
The basal forebrain degenerates in Alzheimer’s disease (AD) and this process is believed to contribute to the cognitive decline observed in AD patients. Impairment in spatial navigation is an early feature of the disease but whether basal forebrain dysfunction in AD is responsible for the impaired navigation skills of AD patients is not known. Our objective was to investigate the relationship between basal forebrain volume and performance in real space as well as computer-based navigation paradigms in an elderly cohort comprising cognitively normal controls, subjects with amnestic mild cognitive impairment and those with AD. We also tested whether basal forebrain volume could predict the participants’ ability to perform allocentric- vs. egocentric-based navigation tasks. The basal forebrain volume was calculated from 1.5 T MRI scans, and navigation skills were assessed using the human analog of the Morris water maze employing allocentric, egocentric and mixed allo/egocentric real space as well as computerized tests. When considering the entire sample, we found that basal forebrain volume correlated with spatial accuracy in allocentric (cued) and mixed allo/egocentric navigation tasks but not the egocentric (uncued) task, demonstrating an important role of the basal forebrain in mediating cue-based spatial navigation capacity. Regression analysis revealed that, although hippocampal volume reflected navigation performance across the entire sample, basal forebrain volume contributed to mixed allo/egocentric navigation performance in the AD group, whereas hippocampal volume did not. This suggests that atrophy of the basal forebrain contributes to aspects of navigation impairment in AD that are independent of hippocampal atrophy.